MSME Strategy in the Digital Era: The Role of Social Media and Environmental Dynamics in Improving Business Performance - Hanum, Nabila Fahhilma; Radianto, Wirawan Endro Dwi; Murwarni, Fulgentius Danardana (Jurnal Aplikasi Manajemen, 2024)
MSMEs play an important role in the national economy, they face significant challenges in the era of digitalization and rapidly changing environmental dynamics. The role of entrepreneurial orientation in MSMEs is very important to encourage business actors to have good business performance. However, previous studies have found inconsistent results in the relationship between entrepreneurial orientation and business performance. This phenomenon creates a research gap, so researchers try to overcome this inconsistency by using the social media adoption variable as a mediating variable. This study aims to test the mediating role of social media adoption and the moderating effect of environmental competitiveness and environmental dynamism in the relationship between entrepreneurial orientation and entrepreneurial marketing on business performance in Micro, Small, and Medium Enterprises (MSMEs). Data analysis was carried out using quantitative methods and sampling techniques using the purposive sampling method processed using SEM-PLS on 200 MSMEs in Indonesia. The research findings show that entrepreneurial orientation and entrepreneurial marketing have a positive and significant effect on MSME business performance. Furthermore, mediation of social media adoption contributes to increasing marketing effectiveness, thereby strengthening business performance. It was also found that environmental dynamism moderates the relationship between entrepreneurial orientation and business performance, while environmental competitiveness has no significant impact on MSME business performance. This study provides practical implications that MSMEs need to be more proactive in adopting social media, utilizing it for brainstorming ideas, seeking information, and developing creative, adaptive entrepreneurial strategies, to be able to increase MSME competitiveness in a changing environment and market, so that they can maintain, even improve their business performance.